An investigation of fiscal policy disclosure - Arifin, Johan; Tower, Gregory; Porter, Stacey (Wiley-Blackwell Publishing Asia, 2012)
This study investigates the level of fiscal policy disclosure within financial statements of Indonesian local governments. Indonesia is a developing country that has recently undergone major state financial reform. Isomorphic institutional theory is adopted as the underlying theoretical framework. There is a high level of communication as measured by the Fiscal Policy Compliance Index (81.2%). Regression analysis shows that the coercive isomorphism variable, measured by number of parliamentarians, is positive and statistically significant predictor of the extent of fiscal policy disclosure. Local governments that have more parliamentarians in their jurisdiction communicate more extensively. In addition, the age of local governments and financial independence variables affect the extent of fiscal policy disclosure in Indonesian local governments.